Tahlîl Tharîqah as-Sam’iyyah wa asy-Syafahiyyah li Fahmi al-Mufradât (Tharîqah al-Bahtsi al-Mukhtalithah) - Mustofa, Zainal; Fatarib, Husnul; Khoirurrijal, Khoirurrijal; Amrullah, M. Kholis; Yaakub, Muhamadul Bakir Hj. (Postgraduate of IAIN Metro Lampung Indonesia, 2023)
The formulation of this research aims mainly to: 1). Knowing the achievement of education through the application of the auditory and oral method in understanding Arabic vocabulary. 2) Identify the development of Arabic language learning by applying the audio and oral method. 3) Identify students' experiences in the Arabic language at school. In this research, the researcher uses the combined methods method and uses the sequential illustration design. Data corrective tests, data qualification, and classical assumptions, so it can be said that the development of students in improving the understanding of Arabic vocabulary at the Global Madani High School Bandar Lampung is very good although it needs evaluation and assistance from the principal The difficulty of students in understanding Arabic lies in the creativity of teachers in teaching Arabic happily and not monotonously with The results of the rehabilitation test in the first and second questionnaires proved the same score 0.848 < 0.70 or reported alpha Cronbach 0.848 is greater than the standard value of Cronbach alpha, and in the classical assumption test it was stated that the first questionnaire Cronbach alpha 0.913 <0.70 was declared correct and in the second questionnaire there was an increase with Cronbach alpha 0.995 <0.70 was declared valid Regarding the topic of student experience in Arabic, it can be seen from the results of student and teacher interviews in the field of study that 80% of students are able to pursue learning well and 20% need help teaching Arabic language with proven data that has been declared correct or accepted by students.